Tafsir Efesus 6: 5-8 Tentang Teologi Kerja Dan Aplikasinya Bagi Pemuda Gereja - Hasahatan Hutahaean; Nurliani Siregar; Desmiyanti Tampubolon (Sekolah Tinggi Teologi Arastamar Bengkulu, 2021)
This article was written to describe the theological understanding of work among church youth and motivate youth to work according to God's word from Ephesians 6:5-8. This article aims to provide an understanding of what the purpose of human work is, provide an understanding of the Biblical concept of work, deepen the knowledge and understanding of congregation members about work theology according to Ephesians 6:5-8 with integrity and a good work ethic, provide an understanding of the contribution of Ephesians 6:5-8 in the relationship between workers and employers. The researcher uses a literature study and interprets the text with the method of theological interpretation. In addition, the author also distributed a questionnaire among church youth who had worked, to obtain a picture of their understanding of work theology. From the results of the questionnaire distributed, it was found that 42.22% of youth really understand work theology, and 52.77%, understand work theology, but in its application, only 37.22% always do the correct life application. So, the researcher conducted deep interviews with several respondents and found that the youth of the HKBP Tanjung Sari church were still lacking in understanding the theology of work. And then they had to be afraid and trembled like Christ and had to be honest and have integrity at workplaces as a service to God.